The effect of educational philosophy in the context of assessment orientation at Colleges of teachers’ education in the Amhara National Regional State, Ethiopia. - Ewunetu, Tiruneh; Sahile, Amare; Tamiru , Tiruwork (Ethiopian Journal of Education Studies, 2025)
This study aimed to examine the effect of educational philosophy on assessment orientation in the teacher education colleges in the Amhara National Regional State. A concurrent mixed methods design was employed to combine strengthens of both quantitative and qualitative data at the same time. For quantitative data, a total of 390 comprehensively selected teacher educators participated in the study. For qualitative data, 48 teacher educators (40 males’ and 8 females) were selected purposefully. Data were collected using questionnaires and interviews. The content validity of the instrument was confirmed by specialists in the fields of education and Cronbach's alpha reliability was checked for items related with assessment orientation and educational philosophy. Quantitative data were analyzed using mean scores, standard deviations, one sample t-test (for implementations of assessment orientation) and MANOVA for three dependent variables of assessment before, during and after instruction, whereas qualitative data were analyzed thematically. The findings revealed that teacher educators misunderstood assessment orientation and failed to differentiate distinct purposes of assessment orientation before, during, and after instruction. The t-test results showed that assessments before and during instruction were not executed as expected. MANOVA also revealed that teacher educators’ philosophy of education significantly contributed to assessment orientation (P< .05). Hence, teacher educators’ philosophy of education plays a significant role in determining their assessment orientation. Therefore, the Regional Education Bureau and colleges of teachers’ education should invest in teacher training and professional development pertinent to the integration of assessment orientation and philosophy of education to improve their practice of assessment orientation in order to enhance students’ learning at CTEs. Keywords: assessment, assessment orientation, educational philosophy, teacher educators, teachers’ education colleges